PENERAPAN METODE QUIZIZZ DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Irawan, Ika Cindrawati; Amirudin, Noor (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2024)
Progresses in data and correspondence innovation have grown quickly in the educational experience. The quizizz strategy can help educators in assessing learning. By carrying out the quizizz technique, it has assisted understudies with further developing their learning results, obviously in a tomfoolery and energizing way.Teachers using the lecture method result in students becoming unenthusiastic and bored. Therefore, this research aims to apply the Quizizz method to the PAI learning process for class VII students at SMP Muhammadiyah 4 Kebomas Gresik. This research uses a qualitative descriptive approach with the type of classroom action research. The informant in this research was a PAI subject teacher and a class VII student at SMP Muhammadiyah 4 Kebomas Gresik. Meanwhile, the technique for determining informants used in this research was purposive sampling. The data collection techniques are observation, interviews and documentation. The results of this research are the application of the quizizz method in learning PAI for class VII students of SMP Muhammadiyah 4 Kebomas Gresik, isolated into four phases, to be specific plot arranging, plan, execution and assessment.In the evaluation stage, it is divided into two categories, the affective domain, in which quizizz has the ability to boost students' enthusiasm for learning. In the psychomotor area, understudies rapidly comprehend PAI material cautiously and completely so this can work on understudies' memory for grasping PAI material.